STRATEGI PROMOSI MELALUI FEEDS INSTAGRAM DAN PAMFLET UNTUK MENINGKATKAN BRAND AWARENESS UMKM MOM’S DESY KITCHEN - Darmawan, Adhicandra; Dermawan, Rizky (Gapenas Publisher, 2024)
Instagram and flyers have become effective promotional tools in increasing brand awareness, especially for Micro, Small, and Medium Enterprises (MSMEs) like Mom’s Desy Kitchen, a home- based culinary business offering a variety of dishes. This article aims to analyze how promotional strategies through Instagram feeds and the use of flyers can enhance brand awareness for Mom’s Desy Kitchen in the local market. The research method involves a case study approach anddirect observation, focusing on visual content, user interaction on social media, and the distribution of flyers within local communities. The results show that regular use of Instagram feeds increases engagement with the audience, while flyers help reach markets with less internet exposure. Both strategies contribute to expanding Mom’s Desy Kitchen’s reach and strengthening its brand image. In conclusion, promotions through Instagram and flyers can help MSMEs increase their brand awareness